Autistic Traits in Patients With Anorexia Nervosa Treated With Intensive Enhanced Cognitive Behavior Therapy ( CBT ‐E): A Prospective Cohort Study - Simona Calugi; Anna Dalle Grave; Mirko Chimini; Gianmatteo Cattaneo; Maddalena Conti; Riccardo Dalle Grave (International Journal of Eating Disorders, 2026)
ABSTRACT Objective This study examined the role of autistic traits in patients with anorexia nervosa receiving an intensive, focused form of enhanced cognitive behavior therapy (CBT‐E). The aim was to assess changes in these traits during treatment and their predictive value for outcomes. Method In this prospective cohort study, 81 patients aged 16–65 years were admitted for intensive CBT‐E. Body mass index (BMI), eating disorder psychopathology, general psychopathology, and functional impairment were assessed at baseline, end of intensive treatment (EOIT), and 20‐week follow‐up. Autistic traits were evaluated using the Autism Spectrum Quotient (AQ) at baseline and EOIT. Results Sixty‐nine patients (85.2%) completed treatment, and 59 among completers (85.5%) attended follow‐up. AQ scores decreased significantly from baseline to EOIT, although the magnitude of the change was small. The AQ global score did not predict dropout. In both intention‐to‐treat and completers' analyses, the AQ global score measured at baseline and at EOIT did not predict eating disorder psychopathology and BMI at EOIT and at follow‐up, respectively. Conclusions In this prospective cohort study, AQ scores decreased significantly over the course of intensive CBT‐E, and autistic traits did not predict treatment outcomes. These findings suggest that intensive CBT‐E produces significant improvements across the main clinical outcomes of anorexia nervosa without requiring systematic adaptations for autistic traits.